From natur(e) to architectural matter: responsive shading system - Oliveira, M. J.; Rato, V.; Leitão, C. (3rd International Conference on Biodigital Architecture and Genetics, 2017)
From the mid XX century, we have seen an increasing interest in exploring a building capacity of changing, of dynamically and automatically responding to the internal and external environments and to different patterns of use. These ideas found its basis on reciprocal relationships between users, spaces and environment. This means that these three factors have direct consequences on each other, affecting reactions, sensations, configuration and even behaviour. The main idea behind this theory is not new; what has changed are the means through which those relationships interact – technology and materials science (Kolarevic, 2014).